1968
DOI: 10.1128/aem.16.10.1503-1506.1968
|View full text |Cite
|
Sign up to set email alerts
|

Routine Identification of Yeasts with the Aid of Molybdate-Agar Medium

Abstract: A large number of yeasts, including a variety of species other than Candida albicans, were isolated from clinical specimens. C. tropicalis and Torulopsis glabrata were each found one-third as frequently as C. albicans. A schema is presented which made possible, by simple procedures, the identification of the great majority of the isolated yeasts. Preliminary isolation and differentiation was aided by the use of molybdate-agar medium. The use of the schema by diagnostic bacteriological laboratories is discussed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1970
1970
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Costa and de Lourdes Branco (2) devised a phosphomolybdate agar on which C. albicans colonies are green and those of other species are blue. At least one other study confirmed the efficacy of this medium (1).…”
mentioning
confidence: 80%
“…Costa and de Lourdes Branco (2) devised a phosphomolybdate agar on which C. albicans colonies are green and those of other species are blue. At least one other study confirmed the efficacy of this medium (1).…”
mentioning
confidence: 80%
“…Molybdate agar has been evaluated as a selective and differential medium for yeasts (2). The differential features of the medium were apparent in this study but not evaluated.…”
Section: Resultsmentioning
confidence: 92%
“…Approximately 50 % of these nonpathogenic Candida species are reactive with one or more of the selected factor sera. However, these saprophytic Candida species constitute less than 1% of all yeastlike fungi found in clinical material (2), and, because accuracy with the factor sera is comparable to that with conventional procedures (96%, Table 5), we do not consider the problem a formidable one.…”
Section: Discussionmentioning
confidence: 99%
“…A portion of a dissertation submitted by the first author to the University of North Carolina in partial fulfillment of the requirements for the degree of Doctor of Public Health in the School of Public Health. 2 Present address: Texas State Department of Health, Austin, Tex. 78756.…”
mentioning
confidence: 99%